Gradient nanostructured surface of a Cu plate processed by incremental frictional sliding. Issue 1 (July 2015) - Hong, C; Huang, X; Hansen, N
Abstract: The flat surface of a Cu plate was processed by incremental frictional sliding at liquid nitrogen temperature. The surface treatment results in a hardened gradient surface layer as thick as 1 mm in the Cu plate, which contains a nanostructured layer on the top with a boundary spacing of the order of 100 nm. The boundary spacing increases with increasing distance from the surface, and is accompanied with a decrease in hardness from 2179±31MPa in the topmost surface layer to 568±10 MPa in the undeformed matrix.